1998
DOI: 10.2139/ssrn.95989
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Hyperinflations and Learning

Abstract: This paper uses a model of boundedly rational learning to account for the observations of recurrent hyperin°ations in the last decade. We study a standard monetary model where the fully rational expectations assumption is replaced by a formal de¯nition of quasi-rational learning. The model under learning is able to match remarkably well some crucial stylized facts observed during the recurrent hyperin°a-tions experienced by several countries in the 80's. We argue that, despite being a small departure from rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
172
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(180 citation statements)
references
References 20 publications
5
172
3
Order By: Relevance
“…For example, one can use surveys on other macroeconomic variables, or use individual surveys to exploit more information than the mean, and one could combine surveys about the expectations of the central bank with those of the private sector in a monetary model. Another promising extension to our research would be to impose rationality bounds on adaptive learning as suggested by Marcet and Nicolini (). We leave these interesting extensions for future research.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one can use surveys on other macroeconomic variables, or use individual surveys to exploit more information than the mean, and one could combine surveys about the expectations of the central bank with those of the private sector in a monetary model. Another promising extension to our research would be to impose rationality bounds on adaptive learning as suggested by Marcet and Nicolini (). We leave these interesting extensions for future research.…”
Section: Resultsmentioning
confidence: 99%
“…In Section , we provide an explicit system of beliefs scriptP in which agents optimally update beliefs according to a special case of equation . Updating rule is more general and nests a range of learning schemes considered in the literature on adaptive learning, for example, least‐squares learning and the switching‐gains learning schemes used by Marcet and Nicolini ().…”
Section: The Modelmentioning
confidence: 99%
“…Examples of papers in this area include Anderson, Hansen and Sargent 1997, Chung 1990, Granger and Deutsch 1992, Hansen and Sargent 1998, Marcet and Nicolini 1997, and Sargent 1998. Related papers in the area of learning are: Bray 1982, Bray and Kreps 1987, Kuan and White 1994, Marcet and Sargent 1989a,b, and Woodford 1990, while a review of the learning literature is in Marimon 1997.…”
Section: Introductionmentioning
confidence: 99%